What motivates academics to engage in industry? The role of spiritual and religious urges - Alireza Babakhan; Mohammad Ali Shafia; Ata Allah Rafiei Atani; Alireza Aliahmadi (European Research on Management and Business Economics (ERMBE), 2020)
This study introduces and applies the Fitrah Tendencies framework to make up for the dearth of studies on academics' urges to play a part in industry. To this end, 62 academics were selected and interviewed based on Lam's (2011) typology as to come up with their main motives for engaging in industry. As per the results, new dimensions including the need for fully understanding God, the desire for doing good deeds, and the freedom felt in the economic environment were added to the previously reported factors.
Keywords: M20; M21; 650; Academic entrepreneurship; Academic researcher; Motivation; The fitrah framework